2019
DOI: 10.1142/s0219061320500087
|View full text |Cite
|
Sign up to set email alerts
|

Definable V-topologies, Henselianity and NIP

Abstract: We initiate the study of definable V-topolgies and show that there is at most one such V-topology on a t-henselian NIP field. Equivalently, we show that if (K, v 1 , v 2 ) is a bi-valued NIP field with v 1 henselian (resp. t-henselian) then v 1 and v 2 are comparable (resp. dependent). As a consequence Shelah's conjecture for NIP fields implies the henselianity conjecture for NIP fields. Furthermore, the latter conjecture is proved for any field admitting a henselian valuation with a dp-minimal residue field. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Hence if Conjecture 6.9 holds, then every valuation ring on a NIP field is henselian, and its residue field is NIP. Moreover, under Conjecture 6.9, any two (externally) definable valuation rings on a NIP field are comparable [38,Corollary 5.4]. In Theorem 6.12 below we show that Conjecture 6.9 also gives rise to a classification of all fields admitting a distal expansion.…”
Section: A Valuation Ringmentioning
confidence: 78%
See 2 more Smart Citations
“…Hence if Conjecture 6.9 holds, then every valuation ring on a NIP field is henselian, and its residue field is NIP. Moreover, under Conjecture 6.9, any two (externally) definable valuation rings on a NIP field are comparable [38,Corollary 5.4]. In Theorem 6.12 below we show that Conjecture 6.9 also gives rise to a classification of all fields admitting a distal expansion.…”
Section: A Valuation Ringmentioning
confidence: 78%
“…This conjecture has numerous consequences; for example, by [38,Proposition 6.3], it implies that every NIP valued field is henselian. In [42,Theorem B] it is shown that if K is NIP and O is a henselian valuation ring of K, then the valued field (K, O) is also NIP.…”
Section: A Valuation Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…Let be a collection of definable subsets of . If the sets in are uniformly definable, and is linearly ordered by inclusion, then the sets and are externally definable [6, Kaplan’s Lemma 3.4].…”
Section: Large Gapsmentioning
confidence: 99%
“…NIP Fields. It is believed that an NIP field is either finite, separably closed, real closed or admits a nontrivial henselian valuation (this conjecture is attributed in [22] to S. Shelah). A characterisation of the subclass of dp-minimal fields is given in [28], which also confirms Shelah's conjecture for the particular case of dp-minimal fields.…”
Section: Preliminaries On Nip Division Rings Of Prime Characteristicmentioning
confidence: 99%